The future exchange rate regime - WILLIAMSON, J. (PSL Quarterly Review, 2014)
When the Committee of Twenty decided to rename the exchange-rate regime rather than reform it, some two weeks after the system had collapsed, it immediately became clear that the ambitious attempt to write a new monetary constitution for the world had failed. If future attempts to reform world monetary relations are not to be equally doomed to failure, a primary requirement is a more realistic approach to this central issue. Accordingly, this paper is devoted to a consideration of the type of approach that wold be required. The author considers what solutions are feasible, managed floating versus crawling par values, the reference rate proposal and reference rates as the basis for a reformed system. JEL: E42, F33